Expat anxieties: Risk and safety in Cape Town, South Africa and Santiago de Chile. (April 2022) - Falkof, Nicky
This article considers 'expatriate' discourses about security in Cape Town, South Africa and Santiago de Chile. The cities themselves have reputations as desirable, beautiful, civilised, modern and welcoming, in contrast to lurid ideas about poverty, crime, filth and corruption that often characterise northern imaginings of the developing world. Yet, their locations within sub-Saharan Africa and Latin America, respectively, nonetheless mark them out as potential spaces of high risk for migrants from the north. In this article, I am interested in the way in which lifestyle migrants to these cities negotiate fears about risk and safety within their new homes. In order to consider this question, I discuss posts on the online messageboards dedicated to these two cities within the popular InterNations 'expat forum, ' as well as a series of interviews with people who use the forum. I use these respondents' discursive constructions of safety, threat, otherness, belonging and the unknowability of the global south city to consider some of the affective underpinnings of this form of privileged migration.